Phage therapy in the management of respiratory and pulmonary infections: a systematic review - Patience Sarkodie-Addo; Abdul-Halim Osman; Bill Clinton Aglomasa; Eric S. Donkor (Therapeutic Advances in Infectious Disease)
Background: Lower respiratory tract infections (LRTIs) pose a significant threat to global health, causing more than 2 million deaths worldwide. This menace is intensified by the alarming increase in drug resistance, which limits the availability of effective antibiotics for bacterial respiratory infections. Consequently, there is an urgent demand for alternative therapeutic options. Phage therapy (PT) has re-emerged as a promising therapeutic approach and as an adjunct to antibiotic treatment. Objective: This systematic review synthesises the application of PT for LRTIs in humans, providing unified and updated data on the evaluation of the safety and efficacy of PT for LRTIs. Design: Systematic review. Data sources and methods: Following the PRISMA guidelines, a comprehensive search strategy was carried out (spanning January 2000 – February 2024) in four databases: PubMed, Scopus, ScienceDirect and Web of Science to retrieve published records of PT for LRTIs in humans only. The reference list of each included study was evaluated for possible inclusion of other relevant articles. Results: Among the 18 records that fulfilled the inclusion criteria, 70 patients were administered PT. Microbiologically, 71.42% ( n  = 50/70) of the patients improved; with either the eradication of the pathogen or a decrease in bacterial load, whilst 15.71% ( n  = 11/70) did not record any improvement. About 5.71% (n = 4/70) recorded a partial/incomplete improvement, whilst 7.14% ( n  = 5/70) of the patients microbiological outcomes were unspecified. Clinically, up to 74.29% ( n  = 52/70) of the patients improved, whilst 10.00% ( n  = 7/70) of the patients showed no improvement. Another 2.86% ( n  = 2/70) recorded partial/incomplete improvement, whilst 12.86% ( n  = 9/70) were uncategorized. Phage titres that yielded positive outcomes ranged from 10 5 to 10 12 PFU/mL. Studies that achieved a substantial phage titre at the site of infection frequently observed notable improvements. Regarding the safety of PT, 77.78% ( N  = 14/18) of the studies did not record any adverse effects after PT was administered, whilst 16.66% ( n  = 3/18) of the studies reported adverse effects. Conclusion: Based on recently published data originating mainly from observational studies, PT has shown considerable efficacy and safety in the treatment of LRTIs. However, there is a lack of uniform methodologies and protocols across different PT cases in the management of LRTIs. Consequently, there is a need for additional clinical studies to establish standardised pharmacokinetic elements and an overall protocol for PT. By doing so, we can fully unlock the potential of PT in effectively managing clinical bacterial infections, including LRTIs.